Fast response in‐plane switching liquid crystal display mode optimized for high‐resolution virtual‐reality head‐mounted display. Issue 4 (12th November 2020) - Matsushima, Toshiharu; Kimura, Shunichi; Komura, Shinichi
Abstract: We propose to apply short‐range lurch control in‐plane switching (SLC‐IPS) as a fast response liquid crystal display (LCD) mode to virtual reality applications, where fast response times and high resolutions are essential. In this study, we discuss the SLC‐IPS electrode structure optimized for high‐resolution virtual reality applications. To maintain transmittance at high resolutions, we developed a one‐sided branch electrode structure with convex parts. The issue of slow response times can be resolved using the convex part of the electrode structure by analyzing the imaginary boundaries characterizing the SLC‐IPS. Thus, a response time of less than 2.2 ms can be obtained over all tones using a 1001‐ppi high‐resolution SLC‐IPS LCD. Abstract : We discuss the short‐range lurch control in‐plane switching (SLC‐IPS) electrode structure optimized for high‐resolution virtual reality applications. To maintain transmittance at high resolutions, we developed a one‐sided branch electrode structure with convex parts. The issue of slow response times can be resolved using the convex part of the electrode structure by analyzing the imaginary boundaries characterizing the SLC‐IPS.